Hebrews as Participatory Exegesis - Ribbens, Benjamin J. (Journal of theological interpretation, 2021)
Matthew Levering and Hans Boersma have outlined participatory or sacramental exegesis as the approach the church fathers used to interpret Scripture, in particular to interpret the Old Testament in light of the New Testament. This article summarizes sacramental exegesis and then explores how Hebrews interprets the Old Testament in a similar way, viewing Old Testament events and people as sacramenta to the New Testament reality (res). Using Hebrews’ discussion of sacrifice, rest, and sonship as examples, the article demonstrates how Hebrews shares the same interpretive patterns as sacramental exegesis and how participatory readings of Hebrews have interpretive power to resolve tensions existing in contemporary Hebrews scholarship.